Operationalising pedagogical content knowledge research in technology education: Considerations for methodological approaches to exploring enacted practice. (16th May 2019) - Doyle, Andrew; Seery, Niall; Gumaelius, Lena
Abstract : Like many areas of curricula internationally, technology education has encountered difficulties in achieving continuity between the rhetoric of prevailing policy and the reality of enacted practices. In technology education, the conceptually oriented nature of curricular goals is theorised to play a significant part in influencing this relationship. One way in which investigations of this relationship have been approached is considering the application of pedagogical content knowledge (PCK) frameworks as a mechanism to understand the interaction of teachers' knowledge and enacted practices. However, understanding from the philosophy of technology, and the technology education literature, suggests that technology education treats knowledge differently to many other disciplines. As a result of this, the interactions between teachers' beliefs and knowledge are theorised to play a more significant role in influencing enacted practice in technology education. Building on this perspective, this article considers the need to investigate the roles of teachers' knowledge and beliefs, and the interactions between these, in the investigation of enacted practice. Further to this, the article problematises the potential for a dominance of exploratory research, though acknowledging the need for research within different paradigms; a common frame of reference is advocated. In advocating a more holistic approach to investigating enacted practice, and the factors which may influence teachers' enactment of teaching practice, it is envisioned that this article takes a step towards methodological coherence regarding the study of enacted practice in technology education.